Edukasi Cegah Obesitas Melalui Media Poster Dan Video Pada Mahasiswa Di Universitas Halu Oleo - Effendy, Devi Savitri; Muchtar, Febriana; Harleli, Harleli; Mutmaina, Iin; Umalia, Wa Ode; Ulfa, Sinar Dwi; Liskasari, Laupi; Rahmawati, Rahmawati; Syahrir, Risma Septiyani; Sulastri, Sulastri (Pakis Journal Institute, 2024)
Obesity among university students has become a serious concern, influenced by insufficient physical activity and unhealthy lifestyles. This health education program aims to raise awareness and promote steps for preventing obesity among students at Halu Oleo University. The program uses a mixed-media approach, including posters, videos, campaigns via Instagram (@23gizieducate), and physical activities such as group aerobics (Senam Bersama). A total of 30 respondents aged 18–25 years (25 females and 5 males) participated in this study. Data were collected through questionnaires distributed online via Google Forms to assess students' knowledge, attitudes, and behaviors regarding physical activity and obesity prevention. The results showed that 56.7% of respondents engaged in physical activity less than twice a week, while 20% did not participate in physical activity at all. The main barriers to exercising included lack of motivation (50%), absence of workout partners (26.7%), and time constraints (23.3%). Nevertheless, 86.7% of respondents expressed a desire to live healthily through regular physical activity. The educational media used, such as Instagram and videos, received positive feedback, with materials perceived as clear, engaging, and easy to understand. This education program successfully increased awareness of the importance of physical activity in preventing obesity among university students. The combination of digital media and direct activities proved effective in enhancing knowledge and encouraging healthier behaviors.